Profesionalisme Public Relations Officers Terhadap Kualitas Pelayanan Era Artificial Intelligence - Naila Desri Anjani; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research aims to analyze the influence of communication competence, organizational culture, and professionalism of public relations officers on the quality of public service in the era of artificial intelligence. The study employs a quantitative method through descriptive analysis, and data collection is conducted online by distributing questionnaires using the Microsoft Forms platform with a Likert scale ranging from 1 to 5. Purposive Sampling is used as the sampling technique, and a total of 100 respondents aged 17-30 who have undergone internship or are currently employed were obtained. The data is processed using the SmartPLS application program with SEM. The research findings indicate that communication competence has a significant impact on the quality of public service. When someone chooses words carefully and treats others with courtesy, it can build trust, respect, and comfort in social interactions. Organizational culture also plays a crucial role in the quality of public service by fostering trust, mutual respect, and cooperation among employees. The study concludes that the professionalism of PROs influences the quality of public service. If the professionalism of PROs improves, the level of service quality will be high, and conversely, if it decreases, the level of service quality will also decline..